(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
The paper deals with the results of comparative and structural analysis of Phragmito- Magno-Caricetea class of coenoflora of Ukraine. For its realization the database of geobotanical releves made by Brawn-Blanquet method, published and kindly placed by A.A. Kuzemko and L.M. Borsukevich was used. It is defined that the coenoflora of the studied class is distinguished by specific wealth and numbers of 635 species that belong to 298 genera and 79 families. A spectrum of the principal families consists of Asteraceae (71 species, 11 %), Cyperaceae (69 species, 10,8 %), Poaceae (61 species, 9,6 %), Apiaceae (28 species, 4,4 %), Ranunculaceae (25, 4,1 %), Lamiaceae (23, 3,9 %), Polygonaceae (22, 3,5 %), Scrophulariaceae (22, 3,5 %), Brassicaceae (21, 3,4 %) and Fabaceae (20 species, 3,3 %). Monocotyledonous are 212 (33,4 %) species, dicotyledonous are 403 (63,5 %). Acidophytes prevail quantitatively (254, 40%) as well as neitrophytes (253, 39,8 %), mesophytes belong to considerable part (187, 29,4 %) and hygromesophytes (139, 21,9 %), hygrophytes are a little less (118, 18,6 %). Among the biomorfa the cryptophytes (269, 42,4 %) and hemicryptophites (236, 37,2 %) prevail quantitatively. In the chorological zonal spectrum boreo-meridional (111, 17,5 %) and boreo-submeridional species (139, 20,6 %) prevail quantitatively, in the regional – hemicosmopolithians (141, 22,2 %), circumpolar (100, 15,7 %), Euro-Asian (130, 20,5 %) and European species (110, 17,3 %) also prevail. Composition of coenoflora includes 264 species: 38 are listed in the Red Data Book of Ukraine, 251 species are included in the Regional Red Lists. Coenoflora of the class consists of 1 species of the European Red List (Astrantia major L.). The biggest ammount of the rare species (56, 21 %) belongs to arctosubmeridional and boreo-submeridional (52, 19,7 %) groups, 62 (23,5 %) species of hemicosmopolithians, 59 (22,4 %) of Euroasian species, 50 (18,9 %) of European. Hygromesophytes are dominant (60, 22,7 %). By the acid regime the subacidophyles and neutrophyles prevail, i.e. 266 species (41,9 %) and 242 species (38,1 %) accordingly, acidophyles are less – 95 (15 %). Concerning generalized salt regime the semieuthophs prevail – 288 species (45,4 %), mesothophs include 140 species (22,1 %) and eutrophic plants –131 (20,6 %). By the content of carbonates in the soil the hemicarbonatophobes there are 332 species (52,3 %), acarbonatophyles are twice less, i.e. 183 (28,8 %). By content of nitrogen available forms the heminitrophyles and nitrophyles prevail – 249 species (39,2 %) and 245 (38,6 %) accordingly. In the coenoflora composition 141 synanthropous species are identified. Among them there are species of the local flora – apophytes 98 (69,5 %) and 43 (30,5 %) of adventive species. Among them there are 25 (58 %) kenophytes, i.e. alien and recently included. And 18 (42 %) archeophytes, i.e. alien species included quite long ago. These species mainly are of Mediterranean and Northern-American origin. It is identified that the most quantity of species is marked in the Magno-Caricetalia order – 595 (94 %), 400 (63 %) species abelong to the Phragmitetalia australis order, 391 (62 %) – to the Nasturtio-Glycerietalia, and the least 251 (40 %) species – to the Oenanthetalia aquaticae order. The problems of plant communities representativeness of the class in the nature conservation of Ukrainian fund econet and ways of protection of its coenoflora are also analyzed.